2020
DOI: 10.3390/en13184821
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Based Vibration Modeling and Solution of High-Speed Elevators Considering the Multi-Direction Coupling Property

Abstract: Vibration of a high-speed elevator is one of the major factors contributing to a safe, stable and comfortable ride. Vibration control and systematic optimization rely on the establishment of an accurate and reliable model. An energy-based vibration model (EVM) is proposed in this paper to describe the multi-directional coupling properties of high-speed elevators. After analyzing the structural and kinematic characteristics, a combination of the kinematic energy, elastic potential energy and virtual works is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Zhang et al [17] have investigated the horizontal vibration dynamics of an elevator car under the infuence of the airfow. Qiu et al [18] have proposed an energy-based vibration model to investigate the coupling vibration characteristics of an elevator, and it was concluded that its accuracy is better than that of the conventional diferential equation-based vibration model.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [17] have investigated the horizontal vibration dynamics of an elevator car under the infuence of the airfow. Qiu et al [18] have proposed an energy-based vibration model to investigate the coupling vibration characteristics of an elevator, and it was concluded that its accuracy is better than that of the conventional diferential equation-based vibration model.…”
Section: Introductionmentioning
confidence: 99%
“…The weight applied to the rope by the traveling cable varies depending on the position of the car-the higher the height of the building, the greater the weight variation. Therefore, it is difficult to compensate for the optimal equivalent weight using the count weight [8,9]. The removal of the traveling cable can reduce the load applied to the rope, thereby increasing the speed and energy efficiency of the elevator [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase of operating speed not only increases the energy consumption of elevators, but also reduces the comfort and safety of riding elevators. [2][3][4]. Therefore, it is important to study the pneumatic characteristics of elevators under different speed operating conditions and design the structure of elevators.…”
Section: Introductionmentioning
confidence: 99%